Effect of Al addition and heat treatment on the microstructures and corrosion resistance of Mg-Cu alloys. (30th January 2022) - Wang, X.W.; Wang, W.; Chen, W.; Chen, D.M.
Highlights: Cu-containing phases exhibit much higher volta potential than Mg17 Al12  and α-Mg. The volume fraction of Cu-containing phase determines the corrosion rate of alloys. Al content and annealing adjust the corrosion performances of Mg-Cu-Al alloys. The alloy is feasible for making fracturing tools. Abstract: The effects of Al content and annealing condition on the microstructures and corrosion performances of Mg-3 wt.%Cu- x Al ( x  = 0, 4 wt.%, 8 wt.%) alloys were investigated. The Mg-3 wt.%Cu alloy contains Mg2 Cu phase, but Al-bearing alloys contain MgAlCu and Mg17 Al12 phases. The Mg2 Cu and MgAlCu phases exhibit much higher Volta potential compared to Mg17 Al12  and α-Mg, and their volume fractions are related to Al content of alloys and annealing condition. The weight loss measurement and electrochemical tests are conducted to explore the corrosion performances of alloys. The close relationship between weight loss rate of alloys and volume fraction of Cu-bearing phases indicates that the corrosion performances of alloys can be controlled by adjusting Al content of alloys and annealing conditions. Graphical abstract: Image, graphical abstract